An Authentication Method for Secure Internet Transaction Using Smart Card and Secure Coprocessor - Ayad, Mustafa Abdsalam (2002)
Authentication is the process of confirming an identity. In the context of network interactions, authentication involves the confident identification of one party by another party. Authentication of users in distributed systems poses special problems because, users lack the ability to encrypt and , decrypt. In most systems today, the user is forced to trust the node he wants to use. In a more satisfactory design, the user carries a smart card with sufficient computing power to assist him. This thesis deals with relatively new methods of authentication using a smart card and secure coprocessor. We analyze two cases to authenticate a client, depending on the smart card usage. The major attacks that affect the smart card and the server are applied to our proposed methods of authentication. The result shows that using the proper system preparation and proper authentication sequence for our methods the effects could be minimized.